1999
DOI: 10.1073/pnas.96.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Alendronate mechanism of action: geranylgeraniol, an intermediate in the mevalonate pathway, prevents inhibition of osteoclast formation, bone resorption, and kinase activation in vitro

Abstract: Nitrogen-containing bisphosphonates were shown to cause macrophage apoptosis by inhibiting enzymes in the biosynthetic pathway leading from mevalonate to cholesterol. This study suggests that, in osteoclasts, geranylgeranyl diphosphate, the substrate for prenylation of most GTP binding proteins, is likely to be the crucial intermediate affected by these bisphosphonates. We report that murine osteoclast formation in culture is inhibited by both lovastatin, an inhibitor of hydroxymethylglutaryl CoA reductase, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
339
1
20

Year Published

2000
2000
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 634 publications
(376 citation statements)
references
References 23 publications
(30 reference statements)
12
339
1
20
Order By: Relevance
“…These observations are consistent with previous studies that have demonstrated that bisphosphonates cause a significant reduction in osteoclast number (Hughes et al, 1995;Fisher et al, 1999). Importantly, studies in human myeloma cells have shown that nitrogen-containing bisphosphonates, including zoledronic acid, also inhibit cell proliferation (Shipman et al, 1997(Shipman et al, , 1998Aparicio et al, 1998;Derenne et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These observations are consistent with previous studies that have demonstrated that bisphosphonates cause a significant reduction in osteoclast number (Hughes et al, 1995;Fisher et al, 1999). Importantly, studies in human myeloma cells have shown that nitrogen-containing bisphosphonates, including zoledronic acid, also inhibit cell proliferation (Shipman et al, 1997(Shipman et al, , 1998Aparicio et al, 1998;Derenne et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…We have also demonstrated that zoledronic acid-induced apoptosis of MCF-7 breast cancer cells can be inhibited by addition of intermediates of the mevalonate pathway, which is consistent with observations in osteoclasts, macrophages and myeloma cells (Luckman et al, 1998;Shipman et al, 1998;Fisher et al, 1999). This pathway has been shown to be important in the posttranslational modification of small GTP-binding proteins including Ras, by the process of farnesylation, and Rho and Rac by geranylgeranylation.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…78 In the case of alendronate at least this results from the inhibition of an unidentified enzyme involved in the conversion of mevalonate to geranylgeranyldiphosphate, the substrate for prenylation of most GTP binding proteins. 33 …”
Section: Other Possible Functions Of Trap Enzymesmentioning
confidence: 99%